The β3 Adrenergic Receptor Agonist BRL37344 Exacerbates Atrial Structural Remodeling Through iNOS Uncoupling in Canine Models of Atrial Fibrillation - Xiaobing Wang; Ruifeng Wang; Guangzhong Liu; Jingmei Dong; Guanqi Zhao; Jingpu Tian; Jiayu Sun; Xiuyue Jia; Lin Wei; Yuping Wang; Weimin Li (Cellular Physiology and Biochemistry, 2016)
Background/Aims: The role of the β3-adrenergic receptor (β3-AR) agonist BRL37344 in atrial fibrillation (AF) structural remodeling and the underlying mechanisms as a therapeutic target were investigated. Methods: Four groups of dogs were evaluated: sham, pacing, β3-AR agonist BRL37344 (β3-AGO), and β3-AR antagonist L748337 (β3-ANT) groups. Dogs in the pacing, β3-AGO and β3-ANT groups were subjected to rapid atrial pacing for four weeks. Atrial structure and function, AF inducibility and duration, atrial myocyte apoptosis and interstitial fibrosis were assessed. Atrial superoxide anions were evaluated by fluorescence microscopy and colorimetric assays. Cardiac nitrate+nitrite levels were used to assess nitric oxide (NO) production. Protein and mRNA expression of β3-AR, neuronal NO synthase (nNOS), inducible NO synthase (iNOS), endothelial NO synthase (eNOS) and guanosine triphosphate cyclohydrolase-1 (GCH-1) as well as tetrahydrobiopterin (BH4) levels were measured. Results: β3-AR was up-regulated in AF. Stimulation of β3-AR significantly increased atrial myocyte apoptosis, fibrosis and atrial dilatation, resulting in increased AF induction and prolonged duration. These effects were attenuated by β3-ANT. Moreover, β3-AGO reduced BH4 and NO production and increased superoxide production, which was inhibited by the specific iNOS inhibitor, 1400w β3-AGO also increased iNOS but decreased eNOS and had no effect on nNOS expression in AF. Conclusions: β3-AR stimulation resulted in atrial structural remodeling by increasing iNOS uncoupling and related oxidative stress. β3-AR up-regulation and iNOS uncoupling might be underlying AF therapeutic targets.